Varicella-zoster virus transverse myelitis in an immunocompetent patient - Alungal, Jemshad; Abdulla, Mansoor C.; Koya, Jassim Mohamad; R, Krishnan (International Journal of Research in Medical Sciences, 2017)
Transverse myelitis is one of the rare neurological complications of Varicella-Zoster Virus (VZV) infection in immuno-competent. We report a 26-year-old immuno-competent gentleman who developed virologically confirmed myelopathy caused by VZV which improved with steroids and acyclovir leaving no residual neurological deficits.